The value of ultrasonography in the diagnosis of early cirrhosis* - Galip ERSÖZ,; Ulus Salih AKARCA,; Funda YILMAZ,; Ömer ÖZÜTEMİZ,; Zeki KARASU,; Tankut İLTER, (Turkish Journal of Gastroenterology, 2019)
-